Cytotoxicity and mode of action of Barrientosiimonas humi extract against breast cancer cell lines - Yeoh, Chiann Ying (2021)
Secondary metabolites from novel extremophilic actinobacteria are found to be potent sources of diverse novel anti-cancer compounds. Currently, development of new and effective cancer therapies remains a challenge due to the problems of systemic toxicity and multidrug resistance in cancer. Barrientosiimonas humi is a novel soil actinobacteria, which was isolated from Barrientos Island, Antarctica. The genus Barrientosiimonas belongs to the order Actinomycetales, which have ability in producing diverse pharmacological compounds. In this study, the cytotoxic effects of ethyl acetate extract and compounds isolated from B. humi were examined using bioassay-guided fractionation, and the molecular pathway involved was also determined. The ethyl acetate extract was obtained from fermentation of B. humi by using solvent extraction and fractionation of the crude extract was conducted via column chromatography. Cytotoxicity was evaluated by using MTT and the iCELLigence Real-Time Cellular Analysis (RTCA) assays. Morphological changes, cell death mechanism, cell cycle profiles and caspases expressions of treated breast cancer cells (MCF-7 and MDA-MB-231) were determined. Furthermore, metabolic alterations induced by B. humi on MDA-MB-231 cells were assessed by Biolog’s Phenotype (PM-M) MicroArray. Major compounds present in B. humi were isolated using different chromatographic techniques. Results revealed that ethyl acetate extract isolated from B. humi (EA-BH) was cytotoxic against both MCF-7 and MDA-MB-231 cells. The extract was then subjected to bioassay-guided fractionation, which yielded four fractions. One of the purified fractions, designated as DCM-F2, exhibited the strongest cytotoxic activity among all the fractions and thereby was selected for further studies. DCM-F2 had selective cytotoxic effect on MCF-7 and MDA-MB-231 cells in concentration- and time-dependent manners. DCM-F2 inhibited cell growth by induction of apoptosis cell death and cell cycle arrest. DCM-F2 triggered apoptosis cell death in both MCF-7 and MDA-MB-231 cells, particularly in the early stage apoptosis. The caspase-3/7 activity in DCM-F2 treated MDA-MB-231 cells showed caspasedependent apoptosis, whereas MCF-7 showed caspase-independent apoptosis. Based on the cell cycle profile, cells treated with DCM-F2 caused significant inhibition of cell cycle progression at 72 h and leading to an increase in the G0/G1 population. PMM assay analysis revealed that the most associated metabolic pathway following treatment of MDA-MB-231 cells with DCM-F2 was glycolysis metabolism. A total of five compounds were successfully obtained. Diketopiperazine, (-)-cyclo (Pro-Tyr) was demonstrated to be the most cytotoxic and selective against MCF-7 and MDA-MB-231 cells compared to other compounds. As a conclusion, EA-BH exhibits significant cytotoxicity in MCF-7 and MDA-MB-231 cells with low toxicity by inducing apoptotic-related pathways, cell cycle arrest and altered glycolytic pathway. These results highlight the potential therapeutic value of B. humi in breast cancer treatment.